2018
DOI: 10.1002/poc.3812
|View full text |Cite
|
Sign up to set email alerts
|

Mixtures of antidepressant amphiphilic drug imipramine hydrochloride and anionic surfactant: Micellar and thermodynamic investigation

Abstract: Aggregation as well as thermodynamic behavior of amphiphilic imipramine hydrochloride (IMH) drug (antidepressant) and anionic surfactant (sodium dodecyl sulfate [NaDS] as well as sodium dodecylbenzenesulfonate [NaDBS]) mixtures as a function of solution composition in aqueous solutions have been evaluated by conductometry method at different temperatures. Surfactant (NaDS and NaDBS) employed in the current study is anionic in nature. Various theoretical models such as Clint, Rubingh, Motomura, and Rodenas were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 102 publications
(37 citation statements)
references
References 67 publications
3
34
0
Order By: Relevance
“…As a result, to attain approximately equal activity, it is repeatedly probable to blend a more surface‐active as well as costly surfactant with a somewhat fewer surface‐active as well as cheaper surfactant in various ratios. In the different applied field, the mixture of surfactants is used instead of single surfactant because of the better electrical and micellar properties of the mixed micelle as compared with the micelle of single surfactant . It is renowned that industrial surfactant systems are a mixture of dissimilar chemical varieties, for example, another surfactant or an amphiphile, electrolytes, dyes, or fillers.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, to attain approximately equal activity, it is repeatedly probable to blend a more surface‐active as well as costly surfactant with a somewhat fewer surface‐active as well as cheaper surfactant in various ratios. In the different applied field, the mixture of surfactants is used instead of single surfactant because of the better electrical and micellar properties of the mixed micelle as compared with the micelle of single surfactant . It is renowned that industrial surfactant systems are a mixture of dissimilar chemical varieties, for example, another surfactant or an amphiphile, electrolytes, dyes, or fillers.…”
Section: Introductionmentioning
confidence: 99%
“…Rub et al found negative values of Δ H 0 c as well as Δ S 0 c for CP of some amphiphilic drugs in the participation of Tw 80 as well as in presence of other additives mixed system . But in case of micellization of amphiphilic drugs, both negative as well as positive values of enthalpy and entropy were found …”
Section: Resultsmentioning
confidence: 97%
“…The obtained positive values of normalΔHc0 in water are due to disruption of the H 2 O structure in the hydrophobic portion of the amphiphilic molecules (Naqvi et al, ). On the other hand, the negative values of normalΔHc0 arise when hydration of water molecules around the polar group of the amphiphilic molecules becomes more significant as compared to the rupture of the H 2 O molecules around the hydrophobic portion (Hoque et al, ; Khan et al, ; Kumar et al, ; Kumar and Rub, ).…”
Section: Resultsmentioning
confidence: 99%